Pelatihan Media Interaktif Mentimeter dalam Memberdayakan Kualitas Teknologi Guru di MTS Arifah Gowa - Ismail; Asham Bin Jamaluddin; Syamsiah; Andi Rahmat Saleh (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
Mentimeter is an interactive application that is very important to use in learning, but receives little attention. The aim of this research is to provide mentimeter training in empowering the quality of teacher technology at MTS Arifah Gowa. The methods used in this research are; a) Observation; b) Discussion and Question and Answer; c) Independent/Structured Assignments; d) Assignment Review; and e) Direct and online consultation. Based on the results of the implementation of this training activity, it can be concluded that there has been an increase in teachers' abilities regarding mentimeter technology. These results can be seen from the evaluation results which show that 87% of MTS Arifah Gowa teachers understand mentimeter technology in the good category.